1992
DOI: 10.7326/0003-4819-117-7-573
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection in Patients with Essential Mixed Cryoglobulinemia

Abstract: The extremely high prevalence of anti-HCV in serum and cryoprecipitate along with the frequently associated serum HCV RNA suggests a close relation between essential mixed cryoglobulinemia and chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
188
0
9

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(203 citation statements)
references
References 22 publications
6
188
0
9
Order By: Relevance
“…The results suggest that in nondissociated cryoglobulins, the anti-hepatitis C antibodies are blocked by antigen, and are therefore unavailable for detection in anti-hepatitis C virus antibody assays. In contrast to these results, one study (36) showed no significant difference between the prevalence of hepatitis C virus antibody in sera and cryoprecipitates. In that study, reduction of the cryoprecipitates with dithiothreitol (DTT) increased the c 100 antibody detected by first-generation ELISA.…”
Section: $ By First-generation Enzyme-linked Immunosorbent Assay (Elimentioning
confidence: 68%
“…The results suggest that in nondissociated cryoglobulins, the anti-hepatitis C antibodies are blocked by antigen, and are therefore unavailable for detection in anti-hepatitis C virus antibody assays. In contrast to these results, one study (36) showed no significant difference between the prevalence of hepatitis C virus antibody in sera and cryoprecipitates. In that study, reduction of the cryoprecipitates with dithiothreitol (DTT) increased the c 100 antibody detected by first-generation ELISA.…”
Section: $ By First-generation Enzyme-linked Immunosorbent Assay (Elimentioning
confidence: 68%
“…Increasing evidence suggests that the hepatitis C virus (HCV) is the causative agent of the so-called mixed cryoglobulinemia (MC) [1][2][3][4] and that it might be involved in the pathogenesis of B cell non-Hodgkin's lymphomas (NHL) complicating MC 5,6 or arising 'de novo'. 7 On the basis of its prevalence among 537 patients with different lymphoproliferative disorders, 180 with MGUS (monoclonal gammopathy of unknown significance), and 470 with B cell NHL, we previously identified the B cell NHL (in particular the immunocytoma) associated with the production of cryoglobulins (in particular type II), as the probable pathogenetic target of HCV.…”
Section: Introductionmentioning
confidence: 99%
“…While mixed cryoglobulins have been described in 50% of patients with chronic HCV infection (l), 53-82% of patients with mixed cryoglobulinemia had chronic HCV infection, and this virus is now considered to be an etiologic agent for mixed cryoglobulinemia (2)(3)(4). Latent autoimmune thyroid disease, glomerulonephritis, polymyositis, and pulmonary fibrosis have been reported in association with HCV (5)(6)(7)(8).…”
mentioning
confidence: 99%